Resilient Development - A Strategy to Diversify Cambodia’s Growth Model : Cambodia Country Economic Memorandum - World Bank (World Bank, Phnom Penh, 2022)
The devastating impact of the Covid-19 pandemic on the Cambodian economy—where the growth slowdown was among the most pronounced in the East Asia and Pacific (EAP) region—lies in the country’s growth generating process. Recent growth has been remarkable, but insufficiently diversified in products, markets, and factor inputs. The diversification problem is rooted in low and declining productivity; low quality and weak export linkages; and high foreign direct investment (FDI) but low domestic investment. Just when past success was fueling high ambitions for future growth—to become upper middle income by 2030 and high income by 2050—the pandemic threatens to put those targets out of reach. Cambodia’s policymakers have the opportunity to build a new and stronger growth path—by enabling productivity of firms and workers, diversifying exports, and harnessing domestic investment. But an ambitious reform agenda is needed—one that focuses on improving capabilities, strengthening regulations, and investing in infrastructure.